Quintuple Helix Analysis of ASEAN Human Securitization Against Covid-19 As Regional Health Insecurity - Jose, Hino (Politeia: Jurnal Ilmu Politik, 2021)
The covid-19 pandemic that was started in March 2020 globally has impacted the mobility and regional interaction on all levels. This disruption managed to hinder regional trade and people-to-people mobility, causing economic fallout in all ASEAN member states. The contraction of the economy and its efforts to recover is dependent on the health policies in ASEAN as the virus remains a threat to human security. This article discussed the research through a qualitative analysis with the data gained from the internet-based and document-based research to explore the substances. The article analyzes through the framework of quintuple helix under the concept of human security agenda to construct the arguments in this paper. This paper concluded that the synergy of all stakeholders from the government, society, industry, academics, and the environment should be harmonized to achieve innovative solutions in regional health securitization. This research has shown that each helices’ role is important to curb the spread of Covid-19 and accelerating the best practices of regional policies with a concrete collaboration from all actors in achieving sustainable solutions.